(3fXGe ZPGFj UMj eJcGeds (3CcKQ ef (B200 (3hUaI dhLHGJ UMjI (B/s - (3Hjf, CfjJGs; (3GdYGeQj, NGdO aGQhbs ((3GdbGgQI (B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY,s, 2002)
(3bGFeI NjGQGJ GdfXGe GdZPGFj GdNGU HeeGQSj GdQjGVI(B.s
Keywords: (3GdJZPjIs -- (3LhGfH UMjIs; (3GdCZPjI hGdUMIs